Heteroxenous coccidia increase the predation risk of parasitized rodents - Vorísek, P; Votýpka, J; Zvára, K; Svobodová, M (Parasitology, 1998)
We have investigated the influence of heteroxenous coccidia (Apicomplexa: Eimeriorina) on the predation risk of intermediate hosts. Voles infected with Frenkelia spp. were found more frequently in buzzards' (Buteo buteo) prey than among snap-trapped rodents. To eliminate the possibility of traps selecting for uninfected rodents, a laboratory experiment was performed. Mice experimentally infected with Sarcocystis dispersa seemed to be more likely caught by the final host, the long-eared owl (Asio otus); this result was confirmed by a mathematical model. Field data confirmed the adaptive value of parasite-induced changes. The increase of predation is directed towards the specific final host only or is non-specific. In the populations studied the probability of predation of parasitized individuals by the specific predator was increased.
Keywords: predátorské chování; Mice; Sarcocystis; rizikové faktory; Host-Parasite Interactions; Predatory Behavior; Animals; myši inbrední BALB C; Raptors; interakce hostitele a parazita; Arvicolinae; zvířata; dravci; myši; Mice, Inbred BALB C; Strigiformes; Risk Factors; Stringiformes